The role of community councils in probation reform - Tyler, Elliot (Probation journal, 2023)
A great benefit exists in giving people on probation the ability to contribute their ideas to the process of ongoing change. The direct experiences of people on probation, and embracing ‘lived experience’, can bring valuable input and unique insights as to what is and is not working within probation. In this comment piece, I outline – through a case study and relevant comment – how service user councils can act as a key reference for the evaluation and improvement of probation services.